Evaluation of two (opx-cpx) pyroxene Geothermometer - Thomas, Harel; Shukla, Satyam; Rana, Haritabh; Soni, Aman; Bidolya, Jyoti; Batri, Rishabh; Mishra, Anju; Chattraj, Rupam (Journal of Nepal Geological Society, 2023)
In the last few decades, for estimation of the original equilibrium conditions of the mantle and deep crustal rocks, several empirical as well as synthetic thermometers have been proposed. Various types of rocks from earth, moon or meteorites contain two coexisting pyroxenes. Petrologists have long recognised the potential of coexisting high Ca and low Ca pyroxenes to yield thermometric calculations. Several models have been proposed for two pyroxene thermometers in the last few decades. The authors have compared ten models of two pyroxene thermometers proposed since 1973. Sixty one (61) sample data of granulites from the global literature were collected and processed through the “Opx-Cpx.EXE” software. We conclude that three models are the most valid and reliable of this kinds of thermometers: Kretz (1982), Bertrend and Mercier (1985) and Nickel and Green (1985).